AKTIVITAS MEREK OLEH REALFOOD MOM COMMUNITY MELALUI WHATSAPP & INSTAGRAM - Nastiti Subiono, Rizki Henggar; Devi, Sofia Primalisanti (Jurnal Insani, 2025)
In the context of an increasingly competitive business environment, companies continuously strive to strengthen their brand recognition through various strategic approaches designed to capture consumer attention. A brand serves as a vital element in differentiating one product from another, making it an essential asset for any organization. This study aims to analyze the brand activation strategies implemented by the Realfood Mom Community through the utilization of online media platforms. Adopting a post-positivist paradigm, this research employs indirect observation and semi-structured interviews with key informants from the Realfood team who are directly involved in the community’s brand activation initiatives. Data collection was guided by structured interview protocols, and  were analyzed using the Miles and Huberman qualitative analysis framework. The findings reveal that the Realfood Mom Community’s brand activation efforts are tailored to meet the needs of its members, remain responsive to current social and digital trends, and consistently align with the overarching vision and mission of the company. These results highlight the strategic role of online-based community engagement in sustaining brand relevance and strengthening brand-consumer relationships in the digital era.